Study of the temporal pattern of nasalization in 4-12 year old cleft palate and normal Persian speaking children - Kowsar Baghban; Farhad Torabinejad; Negin Moradi; Akbar Biglarian (Vesnu Publications, 2012)
Introduction: Hypernasality frequently occurs in children with cleft palate. The patterns of nasalization may differ in various languages. The one of contributive factor to oral-nasal resonance imbalance might be poor timing of velopharyngeal closure in relation to the activity of other articulators. Perceptual judgment has been regarded as the gold standard for rating hypernasality but it has been associated with poor reliability. There has been significant interest in developing acoustic measures to supplement perceptual judgment. The purpose of this study was to measure temporal patterns of nasalization differentiate 4-12 year old children with and without cleft palate and the extent to which vowel context contributes to these temporal differences. Methods and Materials: The study was conducted on 14 cleft palate with or without cleft lip (11 males and 3 females) and 14 normal children (11 males and 3 females).  The total nasalization duration measures were obtained from acoustic waveforms and spectrograms acquired from speech samples (pimip, pamap and pumup) using Praat software. Data analysis was in the significant range of 95% (P < 0.05). Results: Total nasalization duration, as demonstrate by acoustic signals, showed different timing characteristics between children with cleft palate and without cleft palate and across vowel contexts (P ≤ 0.001).  Conclusion: The timing parameters allow us to assume underlying temporal differences in cleft palate and normal Persian speaking children. The longer nasalization durations in children with cleft palate than normal children showed that temporal patterns delayed or deviance in children with cleft palate. Acoustic analysis of temporal pattern useful in survey resonance characteristics in cleft palate and normal Persian speaking children. Keywords: Temporal patterns, Nasalization, Cleft palate, Acoustic analysis, Velopharyngeal insufficiency